First order phase transition during displacement of amphiphilic biomacromolecules from interfaces by surfactant molecules - Ettelaie, Rammile (2014)
The adsorption of surfactants onto a hydrophobic interface, already laden with a fixed number of polymers, is studied using the self consistent field (SCF) calculation method of Scheutjens and Fleer. For polymers having unfavourable interactions with the surfactant molecules, the adsorption isotherms show an abrupt jump at a certain value of surfactant bulk concentration. Alternatively, the same behaviour is exhibited when the number of polymers on the interface is decreased. We show that this sudden jump is associated with a first-order phase transition, by calculating the free energy values for the stable and the metastable states at both sides of the transition point. We also observe that the transition can occur for two approaching surfaces, from a high surfactant coverage phase to a low surfactant coverage one, at sufficiently close separation distances. The consequence of this finding for the steric colloidal interactions, induced by the overlap of two polymer + surfactant films, is explored. In particular, a significantly different interaction, in terms of its magnitude and range, is predicted for these two phases. We also consider the relevance of the current study to problems involving the competitive displacement of proteins by surfactants in food colloid systems.